Abnormal uterine bleeding in perimenopausal age group women: a study on clinicopathological evaluation and management - U., Sreelakshmi; V., Tushara Bindu; T., Subhashini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is the most common and frequent presenting complaint in Gynaecology Outpatient Department in all age groups, especially in perimenopausal women. Objective of present study was clinicopathological evaluation and management of abnormal uterine bleeding in perimenopausal age group women. Methods: The present study was prospective analytical study conducted at Mallareddy Narayana Multi-speciality Hospital, reputed teaching hospital, in Obstetrics and gynaecology department in association with department of pathology from January 2015 to December 2016. Perimenopausal women in age group 45-55 years included in this study. Other age groups with abnormal uterine bleeding, isolated cervical or vaginal pathology, bleeding diathesis, and pregnancy related causes of bleeding excluded from this study. Endometrial tissue collected by sampling procedure such as dilatation and curettage. Proper counselling about management was given to all women related to medical and surgical interventional approaches. Results: A total of 135 women with abnormal uterine bleeding in perimenopausal age were examined after fulfilling criteria during study period of 2 years. The age of participants in mean±SD was 46.68±2.03 years (min 45 years and max 55 years). Maximum number of patients with abnormal uterine bleeding presented in age group of 45-50 years. The most common symptoms were heavy menstrual bleeding (83.7%), followed by frequent menstrual bleeding (26.6%). Proliferative endometrium was the most common histopathological (30.3%) study followed by secretory endometrium (27.4%). Surgical management was given to 94 patients. Conclusions: Heavy menstrual bleeding and frequent menstrual bleeding were mostly correlated with abnormal endometrial histopathological findings in this study. Gynaecologists should pay attention towards these abnormal bleeding patterns along with the evaluation of endometrial tissue for histopathological findings, which will help us to plan for successful management.